Family engagement in the middle: Reaching out to families of English learners. Issue 1 (1st January 2021) - Protacio, Maria Selena; Piazza, Susan V.; David, Virginia
Abstract: At the middle school level, active family engagement is difficult enough with native English speaking families but even more so with parents of English learners (ELs). Using a funds of knowledge approach in this article, we position families as knowledgeable participants with strengths who contribute significantly to their adolescent's academic and overall development. We provide three cases of middle grades teachers who took the initiative to engage with families of ELs. Each teacher utilized different strategies, but they ultimately all increased EL family engagement in their middle school setting. This article shows that EL families will be more engaged when strategies used are more inclusive and responsive to their needs.